Un comentario inédito de José Acosta a la Égloga IV de Virgilio - Martínez Ortega, Ricardo; Izquierdo Izquierdo, José Antonio (1995)
En la Biblioteca Universitaria de La Laguna se encuentra un manuscrito en el que se incluye la edición, traducción y notas de las Églogas y Geórgicas de Virgilio, cuyo autor es el latinista canario José de Acosta. En este articulo nos hemos centrado en el análisis de sus notas a la Égloga IV, situando dicho comentario en la diacronía del virgilianismo filológico español. De nuestro análisis puede desprenderse la función didáctica de este trabajo, que entronca con el comentario que de las Églogas edita en el siglo XVIII el jesuita español Petisco (deudor a su vez del también jesuita Ruée, quien publica en el siglo XVII un comentario a la obra completa de Virgilio en la colección francesa ad usum Delphini de marcado carácter pedagógico), a quien en ocasiones copia literalmente.
There is a manuscript in the Library of the University of La Laguna, whose author is the Canarian latinist José de Acosta. This manuscript contains the edition, transíation and notes of Vergil’s Eclogues and Georgics. Our aim in this article is to analyse Acosta’s notes on Vergil’s Eclogue IV, centring this commentary on the diachrony of the Spanish philological virgilianism. We can deduce from this study tIxe didactic purpose of Acostas work, which is related to the commentary of Vergil’s Eclogues that was published by Petisco, a jesuit, in the eighteen century and Acosta sometimes makes a complete copy of it. In his turn, Petisco is greatly indebted to Ruée, another jesuit, who published a pedagogical commentary of Vergil’s complete works in the French collection ad usum Delphini during the seventeenth century.
Keywords: Acosta, José de; Virgilio Marón, Publio